Analyzing Education Quality in Papua Province Using Education Indicators - Yuni Mariani Manik; Novi Eko Prasetyo; Sulistyo Sulistyo (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to analyze the Net Enrollment Rate (NER), the number of school education facilities at various levels of education, and the student-teacher ratio in Papua Province. The analytical method used in this study is quantitative descriptive data analysis, using a quantitative descriptive method with secondary data from the Central Bureau of Statistics for the 2019-2022 period. To measure the level of education participation in Papua, the School Enrollment Rate (APS) indicator is one indicator that can be used. The school enrollment rate (APS) is the ratio between the number of people who increase at a certain level of education and the number of people in the school-age group that corresponds to that level of education. In addition, the APS indicator can also be used as a parameter to determine the level of educational equity in an area. The results of the analysis show that the net enrollment rate for each age group has decreased by 12.65-22.70%. The number of primary schools in Papua Province has fluctuated, while Madrasah Ibtidaiyah has increased. The number of junior high schools increased while the number of Islamic junior high schools remained the same. The number of senior high schools is dominated by high schools, followed by Islamic high schools, then vocational high schools, Christian high schools and Christian theological high schools. The trend of changes in the ratio of elementary school students has decreased while the ratio of junior and senior high school teachers has increased. In general, the student-teacher ratio in Papua is still relatively low because it exceeds the standards set by the government. This is caused by many factors that still require further research.